Adsorption of quarternized palm kernel shell for fluoride removal - Abu Bakar, Ayu Haslija (2018)
The excess concentrations of fluoride in water for human consumption may cause severe health problems. Among several treatment technologies applied for fluoride removal, adsorption process has been explored widely and proven as an efficient method. An agricultural waste, palm kernel shell (PKS) was quartenized in order to improve the adsorption efficiency as an adsorbent for adsorbing fluoride from waste water by batch and fixed bed column process. Commercial palm kernel shell activated carbon (PKSAC) was used as a comparison to the quaternized palm kernel shell (QPKS). Effect of various factors on the fluoride removal was investigated, such as pH, initial concentration, adsorbent dosage and contact time. Adsorption capacity increased with the increased of adsorbent dosage and contact time. Optimum parameters which resulted in maximum adsorption capacity of 1.7 mg/g by QPKS and 1.3 mg/g by PKSAC was achieved at pH 3 with initial concentration of 20 mg/L, an adsorbent dosage of 8 g/L with contact time of 4 h. The adsorption behavior was further investigated using equilibrium isotherms. In batch process, isotherms such as Langmuir, Freundlich, Redlich-Peterson, and Sips were studied, in which Redlich-Peterson, Langmuir and Freundlich fit well with a coefficient correlation (R2), ranged from 0.95 to 0.99. Kinetic studies, such as pseudo first and second order, Boyd’s model, Elovich model, Double Exponential model and Intraparticle Diffusivities model, were investigated and showed parallel transports exist in the adsorption process and intraparticle diffusion is the rate limiting step for both adsorbents. In fixed bed column process, breakthrough time was affected by bed height and initial fluoride concentration and kinetics studies investigated were Adam-Bohart, Thomas and Yoon-Nelson Model. Regeneration study showed that QPKS performance decreased by 63% compared to PKSAC which decreased by 80% after four cycles of adsorption-desorption. These results suggest that quaterrnized palm kernel shell (QPKS) has the potential to serve as a low-cost adsorbent for fluoride removal from aqueous solutions.